1992
DOI: 10.1128/mcb.12.9.3872
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of a human alpha-tropomyosin muscle-specific exon: identification of determining sequences.

Abstract: The human ac-tropomyosin gene hTM.m has two mutually exclusive versions of exon 5 (NM and SK), one of which is expressed specifically in skeletal muscle (exon SK). A minigene construct expresses only the nonmuscle (NM) isoform when transfected into COS-1 cells and both forms when transfected into myoblasts. Twenty-four mutants were produced to determine why the SK exon is not expressed in COS cells. The results showed that exons NM and SK are not in competition for splicing to the flanking exons and that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
(48 reference statements)
1
25
1
Order By: Relevance
“…These results suggest that the SE element is not involved in the formation of essential secondary structures with other ED 1 exon sequences. Our observations contrast with the usual characteristics of mammalian exon sequences, as manipulations introduced into almost any region of other alternate exons provoked important changes in exon splicing in vivo and, when tested, in vitro (Hampson et al 1989;Streuli and Saito 1989;Libri et al 1990;Black 1991;Tacke and Goridis 1991;Black 1992;Cooper 1992;Cote et al 1992;Graham et al 1992). Thus, the SE element of the fibronectin ED 1 exon is rather exceptional among mammalian exon elements in its ability to efficiently promote 3' splice site recognition even following considerable molecular surgery on flanking exon sequences.…”
Section: The Se Element Is An Enhancer Of Splicingcontrasting
confidence: 54%
See 1 more Smart Citation
“…These results suggest that the SE element is not involved in the formation of essential secondary structures with other ED 1 exon sequences. Our observations contrast with the usual characteristics of mammalian exon sequences, as manipulations introduced into almost any region of other alternate exons provoked important changes in exon splicing in vivo and, when tested, in vitro (Hampson et al 1989;Streuli and Saito 1989;Libri et al 1990;Black 1991;Tacke and Goridis 1991;Black 1992;Cooper 1992;Cote et al 1992;Graham et al 1992). Thus, the SE element of the fibronectin ED 1 exon is rather exceptional among mammalian exon elements in its ability to efficiently promote 3' splice site recognition even following considerable molecular surgery on flanking exon sequences.…”
Section: The Se Element Is An Enhancer Of Splicingcontrasting
confidence: 54%
“…Several studies testify to the importance of exon sequences in splice site selection. Some exon sequences repress the use of adjacent splice sites (Gallego et al 1992;Nemeroff et al 1992;Siebel et al 1992)while other exon elements act positively by stimulating splicing (Reed and Maniatis 1986;Hampson et al 1989;Streuli and Saito 1989;Libri et al 1990;Cooper 1992;Cote et al 1992;Graham et al 1992). Recently, purine-rich elements acting as splicing enhancers have been identified in two m a m m a l i a n alternate exons (Watakabe et al 1993;Xu et al 1993).…”
mentioning
confidence: 99%
“…Recent reports have shown that the SR proteins selectively bind to purine-rich splicing elements present in cellular exons (30,49,50). There are also several examples of negative-acting exon splicing elements (2,4,18,45,55). To date, factors interacting with negative-acting exon splicing elements affecting alternative 3Ј splice site usage in metazoan cells have not yet been reported.…”
mentioning
confidence: 99%
“…The avian troponin T gene contains an optional exon spliced in the embryonic but not the adult heart (41,54). Alpha-and beta-tropomyosin genes contain pairs of mutually exclusive internal exons spliced with strict tissue specificity (5,14,24,25,32). The pre-mRNA encoding calcitonin and calcitonin gene-related peptide contains six exons, one of which (exon 4) is skipped in a few cell types, including neuronal cells.…”
mentioning
confidence: 99%